Optimizing the Shape of Rotor Blades for Maximum Power Extraction in Marine Current Turbines - Esfahani, J.A.; Karbasian, H.R. (Universiti Malaysia Pahang, 2012)
In this paper the shape of rotor blades in Marine Current Turbines (MCTs) are investigated. The evaluation of hydrodynamic loads on blades is performed based on the Blade Element Momentum (BEM) theory. The shape of blades is optimized according to the main parameters in the configuration and operation of these devices. The optimization is conducted based on the ability of the blades to harness the maximum energy during operating. The main parameters investigated are the tip speed ratio and angle of attack. Furthermore, the influence of these parameters on the maximum energy extraction from fluid flow over a hydrofoil is evaluated. It is shown that the effect of the angle of attack on power extraction is greater than that of the tip speed ratio, while both are found to be significant. Additionally, the proper angle of attack is the angle at which the lift to drag ratio is at its maximum value. However, if a proper angle of attack is chosen, the variations in power coefficient would not be effectively changed with small variations in the tip speed ratio.